Litostratigrafia spodnotriasových súvrství Západných Karpát - Mário Olšavský (Geologické práce. Správy)
The nomenclature of Lower Triassic lithostratigraphic units in the Western Carpathians has not been standardized to date. Reference profiles and stratotypes have not yet been established for all Lower Triassic sedimentary sequences. Lithostratigraphic names of Lower Triassic sedimentary sequences are also not consistent in the edition of Regional Geological Maps of Slovakia 1 : 50,000 published by the Dionýz Štúr State Geological Institute. For a better understanding of lithology, facies changes, paleogeography, etc., it is necessary to re-evaluate the knowledge of Lower Triassic sedimentary sequences and their internal content. This paper presents a view of the lithostratigraphic division of the Lower Triassic in the Western Carpathians. It consists of two parts. The first part contains historical contexts of lithostratigraphic divisions used from the beginning of research to the creation of regional geological maps. The second part presents examples of the division of lithostratigraphic units at documented localities, from some tectonic units of the Western Carpathians, prepared on the basis of field geological mapping. The Triassic sedimentary sequence of the Central / Internal Western Carpathians is composed of 3 distinctive formations: Lower Triassic quartzites, Lunz sandstones (Carnian) and Keuper sandstones (Norian). The Lower Triassic sedimentary sequences are due to their extent and lithology, the most significant element among them. Since the 1980s, the name Lúžňa Formation has been used for the Lower Triassic sequence in the Tatricum, Fatricum and Veporicum. However, its lithostratigraphic division is still affected by the use of the older term Werfen Beds / Formation adopted from the Alpine area to the Carpathians, which should not be used. The overlying part of the Lúžňa Formation with a transition to the Middle Triassic carbonate platform, as well as the transitions from Permian sedimentary sequences to the Lúžňa Formation, have not been systematically subjected to detailed study. In the Hronicum unit, the lithostratigraphic division applies a two-part development, as the lower part is siliciclastic with a presumed partly continental development, while the upper siliciclastic-carbonate part has features of marine environments. However, only the informal lithostratigraphic units of the Benkovo and Šuňava Formations have been established to date. The Hronsek Beds have recently been defined between the two formations, which have a much greater thickness in the southern tectonic units (Silicicum). In these southern units, the continental character at the base of the Lower Triassic strata completely disappears, and it even seems that the Triassic sedimentary record has a fully marine character from the beginning. The sedimentary development is more diverse here, and the Lower Triassic has several specific lithological members. Unfortunately, the applied terminology was not adopted from the Hungarian territory completely correctly, and thus it still provides reserves in the interpretation and understanding of its division. The issue of lithostratigraphic division of Lower Triassic sedimentary sequences in the Western Carpathians is still an open topic.